Pengaruh Baby SPA terhadap Kenaikan Berat Badan Bayi di Klinik Cinta Medika 4.0 Parung Panjang Bogor Tahun 2022 - Iis Sumiyati; Moudy E U Djami; Erna J Simatupang; Rangga Pusmaika; Yizri Novrida (Prodi Kesehatan Masyarakat FKM UIN Sumatera Utara Medan, 2023)
Children's growth and development is one of the focuses in health development. Based on a survey of Indonesian nutrition studies, the prevalence of malnutrition in Indonesia is still high. The high number of cases gives an idea that there are still many babies who have growth problems. Such growth is closely related to weight. One of the ways to increase weight is with the baby spa method. The purpose of this study was to determine the effect of Baby Spa on increasing the weight of babies aged 6-12 months at the Cinta Medika 4.0 clinic in 2022. This study uses a quasi-experimental approach with a one-groups pre and posttest research design. The sampling technique is based on the cross-sectional method with a total population of 30 babies and the samples used are 30 babies. Based on the sipel paired test results in the Baby group, the Asymp value was obtained. Sig (2-tailed)=0.000 or pvalue < 0.05, meaning that there is an effect of baby spa on increasing baby weight. Conclusion: The influence of baby spas on the increase in baby weight proves that baby spas increase weight faster in babies.